The impact of Non-Oil exports on economic growth under the trade openness policy in Algeria For the Period 1990-2022 using ARDL model - belghit, hadia; ait-yahia, samir (Journal of Excellence for Economics and Management Research, 2024)
This paper aims to study the impact of non-oil exports on economic growth for the period 1990-2022, which witnessed Algeria moving towards liberalizing foreign trade, by measuring the impact of non-oil exports, the trade openness index, the exchange rate, and foreign direct investment as independent variables on Economic growth as a dependent variable, based on the autoregressive model of distributed time gaps ARDL. The results showed a positive relationship in both long and short term between economic growth and non-oil exports, the trade openness index, and foreign investment, and an inverse relationship in the two terms between the exchange rate and economic growth. In general, it became clear that promoting non-oil exports contributes greatly to raising economic growth rates.